Effect of silver nanoparticles on biofilm forming Pseudomonas aeruginosa Isolates from Menoufia University Hospitals - Amal Makled; Sahar Mohamed; Ahmed Teima; Dalia Mohammed Nabil Shaban; Amal Dawoud (Microbes and Infectious Diseases, 2023)
Background:  Numerous infections can be caused by Pseudomonas aeruginosa, particularly in hospitalized patients. The aim of the study was to estimate the antibacterial and biofilm inhibition effects of Silver nanoparticles (AgNPs) on P.aeruginosa isolates. Methodology: A total of 283 samples were taken from hospitalized patients at Menoufia University Hospitals. P. aeruginosa isolates were identified by standard microbiological methods and VITEK 2 system. Antibiogram and biofilm formation were assessed by disk diffusion and modified congo red agar methods respectively. PslA and lasR genes were detected by conventional PCR. The antibacterial and anti-biofilm effects of AgNPs were also tested. Results: P. aeruginosa isolates represented 16.7% of isolates, 92% of them were resistant to piperacillin and ciprofloxacin. Resistance to aztreonam, piperacillin/tazobactam, cefepime, ceftazidime, and gentamicin were 74%, 72%, 72%, 62%, and 52% respectively.  P. aeruginosa isolates were sensitive to meropenem (68%) and imipenem (60%). Approximately 54% and 44% of the isolates were ESβL and biofilm producers respectively. PslA and lasR genes were found among 52% and 48% of P. aeruginosa isolates respectively. The MIC and MBC of AgNPs ranged from (6.25 to 50 μg/mL), inhibiting 40.9% of biofilms at 6.25 μg/mL and further inhibiting 40.9% of biofilms at 12.5 μg/mL. Conclusion: P. aeruginosa are serious nosocomial pathogens due to high antimicrobial resistance that is mainly due to ESβLs production and biofilm formation. AgNPs exert potent antibacterial and anti-biofilm effects at concentrations of 6.25–50 μg/ml.